Religion and Film: The Commodification of Quranic Verses in Indonesian Religious Films from 2008 to 2020 - Yayan Rahmatikawati; Dadan Rusmana; Akhmad Jauhari (UIN Sunan Gunung Djati Bandung, 2021)
This article describes the use of Quranic verses in Indonesian religious films released from 2008 to 2020. This study investigates Indonesian religious movies based on the Quranic verses, the contexts, and the purposes for which they are used. The theories applied to religious films by Rachel Dwyer (2006) and relations of religion from films by Gregory J. Watkins (2008). The method used in this research is descriptive, in which the researcher interprets the religious film based on text through content analysis. The results show that there are films that use religious interpretation, such asbypresenting cultural values related to religion, encouraging religious life, or using religious critics.